A taxonomic revision of the ecologically important Ochna holstii (Ochnaceae) complex using molecular and morphological data - Toral Shah; Fandey H. Mashimba; Haji. O. Suleiman; Yahya S. Mbailwa; Vincent Savolainen; Isabel Larridon; Iain Darbyshire (Plant Ecology and Evolution, 2023)
Background and aims – Ochna holstii and its allies represent an ecologically important group in a variety of lowland to montane habitats in tropical eastern and southern Africa. Identifying and delimiting species within this group has proved challenging due to a lack of variation in morphological characters. We combine genomic-scale data of multiple accessions per species with morphological data to generate a taxonomic revision for the Ochna holstii complex using a multi-evidence approach. Material and methods – A total of 50 samples representing eight species were analysed using target enrichment and a custom bait kit. Phylogenetic analysis was conducted using the multi-species coalescent model and a concatenation maximum likelihood method, and gene tree discordance was investigated. Herbarium specimens of the O. holstii complex were studied in detail for informative morphological characters, supplemented where possible from field collections, and a full taxonomic revision is provided. Key results – Within Ochna sect. Schizanthera Clade I, our study confirms that all species are monophyletic and supported by morphological data with the exception of O. holstii, which is paraphyletic. A new species, O. mchanga, previously confused with O. polyneura, is described, and the placement of another recently described species, O. maguirei, is confirmed for the first time using molecular data. Conclusion – The widespread montane tree Ochna holstii is non-monophyletic in its current circumscription and likely gave rise to the more range-restricted O. oxyphylla and O. stolzii. We suggest that an integrated taxonomy approach, using both molecular and morphological data, is essential for deciphering difficult species relationships in Ochna.